Total Protein–Chloride Ratio in Pleural Fluid Independently Predicts Overall Survival in Malignant Pleural Effusion at the First Diagnosis - Qiao, Xin; Zhang, Zhi-Rong; Shi, Xin-Yu; Yi, Feng-Shuang (Frontiers in Oncology, 2022)
Objective: Pre-treatment biomarkers to estimate overall survival (OS) for malignant pleural effusion (MPE) are unidentified, especially those in pleural fluid. We evaluated the relationship between OS and total protein- chloride ratio in malignant pleural effusion (PE TPClR). Materials and methods: A retrospective study was undertaken to identify patients from 2006 to 2018 who had pathologically or cytologically confirmed to be MPE and received no tumor targeted therapy. We recorded pre-treatment clinicopathologic characteristics and follow-up status. OS was estimated by the Kaplan-Meier method, the association between variables and OS was evaluated by Cox proportional hazards models. Results: We screened 214 patients who met the eligibility criteria. The optimal cutoff value for the PE TPClR was set at 0.53. Univariate analysis showed that there was a significant correlation between PE TPClR and OS (P < 0.001). Multivariate analysis between OS and the variables selected from univariate analysis showed that the level of neutrophil(N), alkaline phosphatase (ALP), neuron specific enolase (NSE), platelets (PLT), albumin (ALB) in peripheral blood, white blood cells in pleural effusion (PE WBCs) were also independent predictors of OS. Conclusion: In patients with MPE, pre-treatment PE TPClR independently predicts OS. Although further research is necessary to generalize our results, this information will help clinicians and patients to determine the most appropriate treatment for MPE patients.